Improving Internal Audit in the Public Sector - D. R. Giniyatullina (Учёт. Анализ. Аудит)
The transition to a digital economy, as well as structural changes generated in connection with this and a set of theoretical, methodological and practical issues related to the development of organizational and methodological support of subjects of internal financial auditing in public sector organizations, are relevant and most interesting for scientific study. The last decade has undergone a fundamental change in the organization of internal financial audits, associated with the implementation of international norms and standards in the legislation of the Russian Federation. In accordance with the international concept of state internal financial control, the division of internal control and internal auditing functions is carried out. In Russia, such a distinction at the legislative level was made in July 2013 by amending the Budget Code of the Russian Federation and delegating the appropriate budgetary authority to the administrators of the federal budget. The government of the Russian Federation has approved a program to improve the efficiency of public finance management for the period until 2018, which indicates the need to improve the quality of financial management in executive bodies and state (municipal) institutions. The practical implementation of this task is associated primarily with improving the quality of internal financial control and auditing.